1990
DOI: 10.3109/02844319009004516
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Oxygen Tension Measurement for Monitoring Musculocutaneous and Cutaneous Flaps

Abstract: In pigs, latissimus dorsi musculocutaneous island flaps and buttock skin island flaps were raised. Subcutaneous (PscO2) and intramuscular oxygen tension (PimO2) were measured using a non-heated needle electrode before, during and after repeated occlusion of the supplying artery or the draining vein. During arterial and venous occlusion, the tissue oxygen tension in the musculocutaneous flap dropped rapidly. A plateau was reached after 15 min. After arterial occlusion the mean value was 20 mmHg (SEM = +/- 5 mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Recent techniques reported for postoperative monitoring include pulse oximetry,79–91 perfusion photoplethysmography,92, 93 surface temperature measurement,94, 95 fluorometry,95–102 microdialysis,103–106 ultrasound,79, 107–109 implanted (Cook‐Swartz) Doppler probes (see Fig. 2),110–119 laser Doppler flowmetry,120–126 impedance plethysmography,127–129 confocal microscopy,130 nuclear medicine,131–133 subcutaneous pH measurement,95, 134–136 hydrogen clearance,137, 138 externalization of part of a buried flap,122, 139 and white light spectrometry 123…”
Section: Resultsmentioning
confidence: 99%
“…Recent techniques reported for postoperative monitoring include pulse oximetry,79–91 perfusion photoplethysmography,92, 93 surface temperature measurement,94, 95 fluorometry,95–102 microdialysis,103–106 ultrasound,79, 107–109 implanted (Cook‐Swartz) Doppler probes (see Fig. 2),110–119 laser Doppler flowmetry,120–126 impedance plethysmography,127–129 confocal microscopy,130 nuclear medicine,131–133 subcutaneous pH measurement,95, 134–136 hydrogen clearance,137, 138 externalization of part of a buried flap,122, 139 and white light spectrometry 123…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia is defined as a reduction in tissue PO 2 to levels insufficient to maintain cellular function, metabolism, and morphologic structure. The association between tissue PO 2 and tissue viability have been studied previously [4,5,7]. Additionally, at lower arterial PO 2 levels, blood pH has a pronounced effect on the oxyhemoglobin dissociation curve.…”
Section: Discussionmentioning
confidence: 97%
“…The analogous-to-digital (A/D) and inputoutput (I/O) converter board converts the detected analogous signals into digitals for further data processing (interface between software and device subunits). and play a key role in the pathophysiologic cascade after surgical ischemia [1][2][3][4][5][6][7]. Under these conditions, tissue injury is attributable to compromised microvascular blood flow, ischemia, tissue hypoxia, and the resulting consequences [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Traditionally, free tissue transfers are monitored clinically by evaluation of color, capillary response, and bleeding after needle prick. An often-used regime includes evaluation every hour during the first 24 postoperative hours, 8 but other methods of monitoring have shown that vascular compromise may be detected earlier. 9 Flap monitoring should ideally be harmless to patient and flap, reliable and accurate, easy to use and interpret, and give continuous information about the condition of the flap.…”
mentioning
confidence: 99%